Novel Role of Gestational Hydralazine in Limiting Maternal and Dietary Obesity-Related Chronic Kidney Disease - Larkin, Benjamin P.; Nguyen, Long T.; Hou, Miao; Glastras, Sarah J.; Chen, Hui; Wang, Rosy; Pollock, Carol A.; Saad, Sonia (Frontiers in Cell and Developmental Biology, 2021)
Background: Maternal obesity is a risk factor for chronic kidney disease (CKD) in offspring, underpinning the theory of the developmental origins of health and disease. DNA methylation has been implicated in the programming of adult chronic disease by maternal obesity, therefore, DNA demethylating agents may mitigate offspring risk of disease. In rodent models, low-dose hydralazine has previously been shown to reduce renal fibrosis via DNA demethylation. We used mouse models of maternal obesity and offspring obesity to determine whether administration of low-dose hydralazine during gestation can prevent fetal programming of CKD in offspring. Methods: Female C57BL/6 mice received high fat diet (HFD) or chow prior to mating, during gestation and lactation. During gestation, dams received subcutaneous hydralazine (5 mg/kg) or saline thrice-weekly. Male offspring weaned to HFD or chow, which continued until endpoint at 32 weeks. Biometric and metabolic parameters, renal global DNA methylation, renal functional and structural changes, and renal markers of fibrosis, inflammation and oxidative stress were assessed at endpoint. Results: Offspring exposed to maternal obesity or diet-induced obesity had significantly increased renal global DNA methylation, together with other adverse renal effects including albuminuria, glomerulosclerosis, renal fibrosis and oxidative stress. Offspring exposed to gestational hydralazine had significantly reduced renal global DNA methylation. In obese offspring of obese mothers, gestational hydralazine significantly decreased albuminuria, glomerulosclerosis and serum creatinine. Obese offspring of hydralazine-treated lean mothers displayed reduced markers of renal fibrosis and oxidative stress. Conclusion: Gestational hydralazine decreased renal global DNA methylation and exerted renoprotective effects in offspring. This supports a potential therapeutic effect of hydralazine in preventing maternal obesity or dietary obesity-related CKD, through an epigenetic mechanism.